Srovnání regionálních metabolických nádorů mozku (18FDG PET) u vybraných úzkostných poruch PD, OCD, PTSD, agorafobie - Grambal, Aleš; Praško, Ján; Bělohlávek, Otakar; Horáček, Jiří; Raszka, Michal (Psychiatrie (Praha, Print), 2009)
Positron emission tomography (PET) detects indirect signs of higher or lower neuronal activity and we suppose relation between the activity and the brain functions. Though the anxiety disorders have many common characteristics, but there are also some differences. In our work we compare silent regional brain requirements in some anxiety disorders. Patients suffering from anxiety disorders were studied with [ 18 F]-2-fluoro-deoxyglucose positron emission tomography ( 18 FDG PET) scans during resting state (condition of random episodic silent thinking, REST) before systematic treatment. We studied twenty five patients suff- ering from Agoraphobia (AP), twenty one with Panic disorder (PD), forty patient with Obsessive compulsive disorder (OCD) and eleven patients with Posttraumatic stress disorder (PTSD). Data were analyzed using software for statistical parametric mapping (SPM99), for localization of brain regions was used software Talairach deamon (TD) and Analysis of functional neuroimages (AFNI). There was higher uptake of 18 FDG in patients suffering from OCD compared with PD and AP patients in left side basal ganglia. There was also higher uptake of 18 FDG in patients with PD and AP patients compared with OCD patients in right frontal areas. The patients suffering from OCD developed higher uptake of 18FDG compared with PTSD patients in middle temporal gyrus bilaterally. PTSD patients showed higher uptake of 18 FDG in comparison with OCD patients in right anterior cingulate. There was higher uptake of 18 FDG in PD and agoraphobia patients in comparison with PTSD patients in right inferior temporal gyrus. There were differences in regional brain activities in 18FDG PET scans between various types of anxiety disorders. The differences could be related to various clinical pictures of these disorders. These results can help in searching of new mechanisms and strategies in the treatment.
Keywords: functional brain imaging (FBI); positron emission tomography (PET); random episodic silent thinking (REST); anxiety disorders (AD)